“A shameful and uncivilized spectacle”: Taxibuses, students, and the conflicted road to deregulation in Pinochet’s Chile, 1975–1978 - Chastain, Andra B. (The Journal of Transport History, 2021)
Abstract: As the military regime of Augusto Pinochet deregulated urban transportation in the late 1970s, controversy flared over a popular mode of urban transit called a taxibus, a small bus with a higher fare than a full-sized bus. This article utilizes newspaper sources to examine the struggles that played out between the taxibus industry, the government, and passengers in the midst of shifting policies. It focuses in particular on controversies surrounding students and youth on taxibuses. The article argues that taxibuses became an object of contention because they occupied an ambiguous space in terms of social class, they displayed the military government’s struggle to provide sufficient transportation and, finally, because bus owners, drivers, and passengers resisted deregulation during this period. This study contributes to our understanding of urban transit in the Global South by shifting attention to small-scale bus entrepreneurs, who occupied an important market in Latin American cities.
Code: The Journal of Transport History
Keywords: Business history in Latin America; Neoliberalism; Public Transit; Santiago; Youth